A causal relationship model of factors influencing glycemic control among pre-diabetes in Phrom Phiram district Phitsanulok province, Thailand: 10.55131/jphd/2025/230306 - Pongsripracha, Kaelyn; Suphunnakul, Pattama (Journal of Public Health and Development, 2025)
This research aimed to study the causal relationships model of the factors influencing glycemic control among pre-diabetes population in Phrom Phiram district, Phitsanulok province. Determining the sample size under the assumptions of the structural equation analysis. The sample consisted of 530 participants, who were recruited by a multistage sampling. Data were collected by questionnaire with reliability value between 0.83- 0.95. Data were analyzed using descriptive statistics and Structural Equation Model (SEM) by LISREL 8.52 software. The study results revealed that 530 participants were Thai (80.8%), Lao Krang ethnic group (14.3%), and Thai of Chinese origin (4.9%) respectively. The majority of participants were female (58.5 %), The mean age was 49.59 years and S.D. of 7.15. 42.5% had primary school level of educational. The mean income was 10,000 bath and S.D. of 7,243.84. 76.6% had duration of pre-diabetes 1-6 years, 77.2% had a family history of diabetes and the mean fasting blood sugar level was 112.57 mg./dl. and S.D. of 8.80. Based on the analysis, a structural equation model that fit to the data was obtained with Chi-Square/df =1.17, P-value=0.0576, GFI=0.99, AGFI=0.97, SRMR=0.030, RMSEA=0.018 and CN= 706.08. A causal relationships model showed that social support explained the variance in health literacy at 46%. Meanwhile, social support, attitude towards glycemic control, norm, and health literacy co-explained the variance in intention at 100%. Then, health literacy, self-efficacy, and intention co-explained the variance in glycemic control behavior at 40%. And glycemic control behavior explained the variance in blood sugar levels at 100%. In conclusion, social support was the most important factor on health literacy. Meanwhile, the health promotion focused mainly on self-efficacy, intention, and health literacy toward glycemic control behavior. That could help to control blood sugar levels of pre-diabetes.